Approximately n-secting an angle - Kim, Seok Woo; Paeng, Seong-Hun; Cho, Hee Je (Information processing letters, 2007)
It is a well-known fact that there exists an angle that cannot be trisected with a straightedge and a compass. In general, it is impossible to divide an arbitrary angle into n-angles equally with only a straightedge and a compass, where n is a positive integer. We give an efficient algorithm to divide an arbitrary angle into n-angles almost equally with only a straightedge and a compass. Using this method, we can construct an almost regular n-gon for arbitrary n.